2018
DOI: 10.18632/oncotarget.25147
|View full text |Cite
|
Sign up to set email alerts
|

ERβ alters the chemosensitivity of luminal breast cancer cells by regulating p53 function

Abstract: Estrogen receptor α (ERα)-positive breast cancers tend to develop resistance to both endocrine therapy and chemotherapy. Despite recent progress in defining molecular pathways that confer endocrine resistance, the mechanisms that regulate chemotherapy response in luminal tumors remain largely elusive. Luminal tumors often express wild-type p53 that is a major determinant of the cellular DNA damage response. Similar to p53, the second ER subtype, ERβ, has been reported to inhibit breast tumorigenesis by acting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 75 publications
3
11
0
Order By: Relevance
“…Although ERα and ERβ are encoded by two different genes, they share 96% and 58%–60% homology in the DNA-binding domain and the ligand-binding domain of ERα, respectively 16 41. Despite sharing similar structures and mechanisms of action, the two ER subtypes evoke distinct transcriptional responses and therefore influence cancer cellular processes differently, suggesting independent roles in therapy resistance 42…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ERα and ERβ are encoded by two different genes, they share 96% and 58%–60% homology in the DNA-binding domain and the ligand-binding domain of ERα, respectively 16 41. Despite sharing similar structures and mechanisms of action, the two ER subtypes evoke distinct transcriptional responses and therefore influence cancer cellular processes differently, suggesting independent roles in therapy resistance 42…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, some studies have demonstrated ERβ positivity to be correlated with a more aggressive clinical outcome15 and with the proliferation marker, Ki-67 43–45. ERβ has also been identified as a novel activator of wild-type p53-dependent transcription, which leads to poorer survival of luminal breast cancer cells 42 46–50…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, in conditional ERβ and p53 KO mice, Bado and colleagues demonstrated that a concomitant loss of ERβ and p53 induced early onset of basal-like mammary tumors [ 176 ]. In two recent independent publications, ERβ was shown to interact with p53, reduce p53–ERα binding affinity, and antagonize transcription regulation by p53–ERα [ 177 , 178 ]. Thus, if there is competitive binding between the ER proteins with p53, it has been suggested that the ratio of ERβ and ERα may affect estrogen responsiveness in breast cancer [ 178 ].…”
Section: The Connection Between P53 Status and Responsiveness To Fmentioning
confidence: 99%
“…In two recent independent publications, ERβ was shown to interact with p53, reduce p53–ERα binding affinity, and antagonize transcription regulation by p53–ERα [ 177 , 178 ]. Thus, if there is competitive binding between the ER proteins with p53, it has been suggested that the ratio of ERβ and ERα may affect estrogen responsiveness in breast cancer [ 178 ]. The pro-apoptosis response of ERβ in breast cancer cells also involved epigenetic changes in the methylation of histones affecting gene regulation and, hence, cellular activities of the cells [ 177 ].…”
Section: The Connection Between P53 Status and Responsiveness To Fmentioning
confidence: 99%
See 1 more Smart Citation